2014
DOI: 10.1038/nature13839
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal–endothelial transition contributes to cardiac neovascularization

Abstract: Endothelial cells contribute to a subset of cardiac fibroblasts by undergoing endothelial-to-mesenchymal-transition, but whether cardiac fibroblasts can adopt an endothelial cell fate and directly contribute to neovascularization after cardiac injury is not known. Here, using genetic fate map techniques, we demonstrate that cardiac fibroblasts rapidly adopt an endothelial cell like phenotype after acute ischemic cardiac injury. Fibroblast derived endothelial cells exhibit anatomical and functional characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
261
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(273 citation statements)
references
References 40 publications
9
261
3
Order By: Relevance
“…This possibility is unexplored in the adult heart but may reconcile the apparent differences between lineagetracing studies on the origin of the cardiac fibroblast. In a final twist, evidence has recently emerged that adult myofibroblasts can undergo mesenchymal-to-endothelial transition (MEndT) and adopt an endothelial phenotype in an acute cardiac ischemia setting (Ubil et al, 2014). The transition appears to be complete, with myofibroblast-derived endothelial cells exhibiting the functional characteristics of native endothelial cells.…”
Section: Origins and Plasticity Of Cardiac Fibroblastsmentioning
confidence: 99%
“…This possibility is unexplored in the adult heart but may reconcile the apparent differences between lineagetracing studies on the origin of the cardiac fibroblast. In a final twist, evidence has recently emerged that adult myofibroblasts can undergo mesenchymal-to-endothelial transition (MEndT) and adopt an endothelial phenotype in an acute cardiac ischemia setting (Ubil et al, 2014). The transition appears to be complete, with myofibroblast-derived endothelial cells exhibiting the functional characteristics of native endothelial cells.…”
Section: Origins and Plasticity Of Cardiac Fibroblastsmentioning
confidence: 99%
“…GAGs, glycosaminoglycosans. environmental cues, interstitial cells exhibit phenotypic changes (84)(85)(86), leading to transitions from inflammatory to reparative phenotypes (87). Through their transient induction and incorporation into the matrix, matricellular proteins may play a critical role in regulating cell differentiation, contributing to the cellular plasticity observed in healing tissues through direct actions and via modulation of growth factor-mediated pathways.…”
Section: Ecm During the Proliferative Phase Of Infarct Healingmentioning
confidence: 99%
“…More recent studies in the heart have shown that the Col1a2 promoter drives expression specifically in fibroblasts, so these mice may represent a useful model for selective genetic manipulation of fibroblasts and myofibroblasts in the heart [145][146][147]. A drawback of the Col1a2 approach however is that it is not selective for fibroblasts in the heart over other sources of fibroblasts (e.g.…”
Section: Cardiac Fibroblast-specific Genetic Modelsmentioning
confidence: 99%